Analisis Penerapan Konsep Economic Value of Time Sebagai Kritik Terhadap Time Value of Money - Yuliana Dia Putri (Business Finance Analyst Co., 2025)
Abstract : The development of Islamic finance theory has become a hot topic of discussion, including the debate on the concept of Time Value of Money. This research aims to understand the concept of money in conventional and Islamic financial systems, the basic principles of Time Value of Money, and the concept of Economic Value of Time. The research method used is qualitative, and data collection is done through literature review and academic studies. The results of the research show that in the conventional financial system, money is considered as a commodity like any other tradable goods and services, which can be bought, sold, and used for speculation, while in Islam, money is viewed as something that cannot be hoarded or wasted, and it is not considered a commodity for trading. The concept of Time Value of Money states that the utility of money today is higher than its utility for money with the same amount in the future, while the Economic Value of Time emphasizes that time itself has economic value, not the money that has time value. Keywords : Time Value of Money, Economic Value of Time, Money, Islam, Conventional.